Preparation of hydrogels by photopolymerization of acrylates in the presence of Type I and one-component Type II photoinitiators - Karaca, Nurcan; Temel, Gokhan; Balta, Demet Karaca; Aydin, Meral; Arsu, Nergis (ELSEVIER SCIENCE SA, 2010)
Hydrogels were prepared by photoinduced polymerization of poly(ethylene glycol)monoacrylate (PEGMA) and poly(ethylene glycol)diacrylate (n=200 and 700) (PEGDA) with Type 1, 1-[4-(2hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propane-1-one (1-2959) and one-component Type 11 initiators: (9-oxo-9H-thioxanthen-2-yloxy)-acetic acid (TXOCH2COOH) and (9-oxo-9H-thioxanthen-2yloxy)-sodium acetate (TXOCH2COO-Na+). The swelling properties of hydrogels were investigated and observed to be excellent. Smooth morphology and no phase separation were observed from SEM micrographs of the hydrogels. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Free radical polymerization; Hydrogel; Photo polymerization; Type II photoinitiator; FREE-RADICAL POLYMERIZATION; ACID; SYSTEMS; Chemistry